Cerebellar Dysfunction in a Patient with HIV - Fernando Gonzalez-Ibarra; Waheed Abdul; Sahar Eivaz-Mohammadi; Christopher Foscue; Srinivas Gongireddy; Amer Syed (Case Reports in Neurological Medicine, 2014)
A 50-year-old AIDS patient with a CD4 T-cell count of 114/mm3 was admitted with cerebellar symptoms of left CN XI weakness, wide-based gait with left-sided dysmetria, abnormal heel-knee-shin test, and dysdiadochokinesia. MRI showed region of hyperintensity in the left inferior cerebellar hemisphere involving the cortex and underlying white matter. Serological tests for HSV1, HSV2, and syphilis were negative. Her CSF contained high protein content and a WBC of 71/mm3, predominantly lymphocytes. The CSF was also negative for cryptococcal antigen and VDRL. CSF culture did not grow microbes. CSF PCR assay was negative for HSV1 and HSV2 but was positive for JC virus (1,276 copies). The most likely diagnosis is granule cell neuronopathy (GCN), which can only be definitively confirmed with biopsy and immunohistochemistry.